Analisa Aplikasi Teknologi Informasi dan Strategi Bisnis Perusahaan Agrobisnis - Buhori Muslim (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Running a business requires the right strategy so that the business runs well and is profitable, specificbusiness strategies, technology applications and information systems (TSI) are the most expected support andbecome a solution. Indonesia and Pagar Alam City in particular are agricultural areas, currently in Pagar Alam theagricultural business is managed efficiently in an agribusiness manner, the object of research is a combination ofcitrus agribusiness companies, zalacca agribusinesses, avocado agribusinesses and so on. From this research, theinternal and external conditions of agribusiness companies have been generated, in terms of business and technologyand information systems (TSI), the next step is to evaluate and provide recommendations for business developmentstrategies in accordance with the habits of agribusiness companies. Where the strategic proposals produced by thisstudy include technology and information systems in the form of electronic proposals (the use of cloud computing)as well as a portfolio of technology and administrative applications that are able to support the implementation ofagribusiness company business processes. For technology management strategies and information systems in theform of a list of proposed types of business activities that can increase the suitability and maturity of agribusinesscompany business strategies.